(untitled) (Ustozlar uchun, 2026)
planning as the "original oil city," where oil extraction and urban development have been thoroughly intertwined economically, politically, and physically in the city’s fabric (Blau, 2018). Located on the Absheron Peninsula along the Caspian Sea, Baku covers over 2,130 square kilometers and is divided into 11 administrative districts (Presidential Library of Azerbaijan, n.d.). The city proper is officially home to 2.4 million people, though unofficial estimates suggest the metropolitan population ranges from 3.8 to 4.2 million, representing approximately 35-40 percent of Azerbaijan’s total population (Valiyev, 2013).